A novel chitosan-biochar immobilized microorganism strategy to enhance bioremediation of crude oil in soil. (February 2023) - Liu, Qiyou; Wang, Yaru; Sun, Shuo; Tang, Fang; Chen, Hongxu; Chen, Shuiquan; Zhao, Chaocheng; Li, Lin
Abstract: The chitosan-biochar composite is a clean and environmentally friendly immobilized microorganisms carrier. In this study, the chitosan-biochar composite as a carrier to immobilize a compound microbial agent contained Pseudomonas aeruginosa and Bacillus licheniformis, and investigated its role in the remediation of oil-contaminated soil. When using 1% (v/v) acetic acid, 3% (m/v) chitosan solution, 0.1% biochar, 4% (v/v) NaOH solution, freeze-drying 6 h, the optimal chitosan-biochar composite material could be obtained. The specific surfacearea of the material increased to 1.725 m 2 /g and the average pore size also increased from 130.2260 nm to 165.2980 nm after the addition of biochar through the analysis of specific surface area and pore size, which enlarged the contact area of microorganisms and crude oil with the material. SEM showed that the bacterial successfully adhered to the surface and internal of the material. Using FTIR, the results showed that the synthesis of composite carrier material was the covalent combination of –NH2 on chitosan and –COOH on biochar, forming a new chemical bond –NH–CO-. After 60 days of remediation of oil-contaminated soil, the removal rate of crude oil by chitosan-biochar composite immobilized microorganism method was 45.82%, which was 21.26% higher than that of natural remediation. Simultaneously, several oil-degrading bacteria increased at genus level, including Nocardioides (26.79%–33.09%), Bacillus (3.01%–4.10%), Dietzia (1.84%–5.56%), Pseudomonas (0–0.78%), among which Pseudomonas belongs to exogenous bacteria. The results indicated that the chitosan-biochar composite material has high application value in removing crude oil, and further provides a new strategy for bioremediation of oil-contaminated soil. Graphical abstract: Image 1 Highlights: The optimal chitosan-biochar composite material was prepared for immobilized microorganisms. A composite microbial agent contained Pseudomonas aeruginosa and Bacillus licheniformis was used. The immobilized microorganism strategy can effectively remove crude oil from oil-contaminated soil. The combination of material adsorption and biodegradation accelerated the remediation of oil-contaminated soil. The chitosan-biochar composite material immobilized microorganisms reshaped the microbial community structure in soil.